Factors Associated With Undergraduate Nursing Students' Academic and Clinical Performance: A Mixed-Methods Study - Fooladi, Ensieh; Karim, Md Nazmul; Vance, Sheila; Walker, Lorraine; Zanjani, Maya Ebrahimi; Ilic, Dragan; Brand, Gabrielle (Frontiers in Medicine, 2022)
Background: There is conflicting and limited information regarding factors that influence undergraduate nursing students’ academic and clinical performance prior to entry to practice. Objective: To identify factors influencing the academic and clinical performance of undergraduate nursing students throughout the course. Design: Mixed-methods study utilising a retrospective cohort and a qualitative study. Setting: Monash University, Melbourne, Australia. Participants: Longitudinal existing data of nursing undergraduate students who commenced in 2017 (n=176) and 2018 (n=76), and two focus groups with final year nursing students, were analysed. Methods: Retrospective students records was used to determine students’ academic and clinical performance using weighted average mark (WAM) of the theoretical and clinical components of the curriculum, separately. The WAM considered the year level of each unit, and scored out of 100. Multivariate linear regression was used to determine predictor factors of academic and clinical performance. Variables include entry cohort (with no previous nursing qualification vs diploma of nursing), admission category (domestic vs international), campus (metropolitan vs outer metropolitan) and secondary school (year 12) results. Two focus group discussions were conducted and thematically analysed. Results: More than two-thirds of students were aged 18-20 years and mainly female. Almost 20% of the participants were international. Students with higher secondary school (year 12) results and studying at the outer metropolitan campus achieved a higher academic performance while international students had significantly lower academic performance compared to domestic students. Students with a previous diploma of enrolled nursing and international students had lower clinical performance. Students identified that a comprehensive orientation, interactive curriculum, formal and informal support structure and educator qualities influenced their academic and/or clinical performance. Conclusions: A supportive educational environment with an interactive curriculum may enhance students’ academic and clinical performance and readiness for practice. Furthermore, targeted interventions for international students, those with lower secondary school (year 12) results, and those with a former diploma of nursing, may be required to increase academic and clinical performance.